OPERATIONAL PERFORMANCE OF ICICI BANK - Dr. V. Sivakumar, Dr. K. Devanadhen (International Journal of Advanced Science and Technology, 2020)
The development of a country is integrally linked with the development of banking. The study mainly analyses the operational performance of ICICI Bank for the period from 2011 to 2019. The study covers the key responsibility areas of deposit mobilization, credit deployment, non-performing assets, profitability and productivity. The deposit mobilization has registered growth of 289 per cent and business per branch has almost quadrupled during the study period. ICICI bank intensify its efforts to effectively and efficiently manage the NPA in the years to come, it may have to lose precious capital resources and eventually end up in red.